Improvement of the Internal Combustion Engine Sleeve Spring Packets Equipped Coupling Calculation Model - Protsenko Vladyslav; Rusanov Sergiy; Kliuev Oleg; Voitovych Olha; Protasov Roman (Journal of Mechanical Engineering)
The presented studies made it possible to clarify the calculation model of the diesel engine clutch with packages of sleeve springs. The stressed state of the spring packets is considered, while it is proposed to place the point of application of the radial force, which bends the spring package, in the zone of its greatest flexibility. Calculations performed according to the obtained expressions showed a coincidence with the results of experimental studies by other authors within 4% and with simulations conducted using automated design systems.